PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM EKSEKUSI OBJEK JAMINAN FIDUSIA OLEH PERUSAHAAN PEMBIAYAAN PASCA KELUARNYA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 - Rinaldi Aidil Oswan; Firdaus Firdaus; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Legal Protection for Consumers in the Execution of Fiduciary GuaranteeObjects by Financing Companies After the issuance of the Constitutional CourtDecision Number 18/PUU-XVII/2019 is interesting to do in the form of a thesis.First, the considerations and decisions of the Constitutional Court's decision havefundamentally changed the concept of default and the execution of fiduciaryguarantees which have been practiced for more than 10 years (since the 2009Fiduciary Security Law was enacted). Second, the Constitutional Court's DecisionNo. 18/PUU-XVII/2019 has created a debate about the pros and cons amongacademics and practitioners. Third, there are different interpretations by judgesin interpreting the considerations and decisions of the Constitutional CourtDecision. Starting from these legal issues, the writing of this thesis aims: First, tofind out and analyze the legal protection for consumers in the execution offiduciary guarantee objects by the Financing Company before the issuance of theConstitutional Court's Decision No. 18/PUU-XVII/2019. Second, to find out andanalyze the legal protection for consumers in the execution of fiduciary guaranteeobjects by the Financing Company after the issuance of the Constitutional CourtDecision No. 18/PUU-XVII/2019.Using a normative juridical research method with a statutory, conceptualand case approach, the results of the study show: First, legal protection forconsumers in the execution of fiduciary guarantee objects before the issuance ofthe Constitutional Court Decision No. 18/PUU-XVII/2019 has 4 maincharacteristics: (a) in a fiduciary agreement, the determination of default occurswhen the debtor is negligent with the passage of time specified in the agreement;(b) in a fiduciary agreement, if the debtor is in breach of contract, the fiduciaryrecipient has the right to execute and sell objects that are the object of thefiduciary guarantee on his own power (parate execution) without going through acourt decision; (c) in the agreement and execution of fiduciary guarantees basedon the provisions of Article 15 and Article 29 UUJF, the position of the parties isnot balanced where the debtor is in a weak position; and (d) in the execution offiduciary guarantees based on the provisions of Article 15 and Article 29 of theJOM Fakultas Hukum Universitas Riau Volume X No. 1 Januari – Juni 2023 Page 2UUJF, legal protection for consumers is weak so that there is the potential forviolations of consumers' rights to comfort, security, and safety in consuminggoods and/or services. Second, legal protection for consumers in the execution offiduciary guarantee objects after the issuance of the Constitutional CourtDecision No. 18/PUU-XVII/2019 has 5 main characteristics: (a) in a fiduciaryagreement based on the provisions of Article 15 paragraph (3) of the UUJF, thedetermination of default cannot be determined unilaterally by the creditor basedon a clause in the fiduciary agreement except on the basis of an agreementbetween the creditor and the debtor or on the basis of legal remedies thatdetermine that a default has occurred; (b) in the execution of a fiduciaryguarantee based on the provisions of Article 15 paragraph (2) of the UUJF, thecreditor must obtain a court decision before carrying out the execution if there isno agreement on default and the debtor object to voluntarily submitting the objectthat becomes the Fiduciary Guarantee; (c) in the agreement and execution offiduciary guarantees based on the provisions of Articles 15 and 29 of the UUJF,the parties are in a balanced position; (d) in the execution of fiduciary guaranteesbased on the provisions of Article 15 and Article 29 of the UUJF, consumers getstrong legal protection so as to minimize the potential for violations of consumerrights to comfort, security, and safety in consuming goods and/or services; and (e)there are still differences of interpretation by the court in deciding cases ofexecution of fiduciary guarantees after the Constitutional Court DecisionNo.18/PUU-XVII/2019.Keywords: Legal Protection, Consumer, Contitutional Court Decision No18/PUU-XVII/2019.